(untitled) (LACCEI, 2024)
The cracks by Plastic Contraction are a pathology of the rigid pavements (hydraulic) that are studied in the present work that aims to identify if the vegetable fibers of the American Agave L. They control the frequency of cracks by plastic shrinkage surface of rigid pavements. For this, four test cloths were prepared. To the different hydraulic concrete panels were added the fibers Agave Americana L. in proportions of 0, 0.5, 0.75 and 1.0 percent of the total volume of concrete. After finishing, the presence of cracks during the setting period was evaluated with the use of a comparator microscope and a ruler. Fissure data were evaluated with an experimental design of separate samples. The results were obtained that the concrete added with 0.75 and 1.0% of Agave Americana L. fibers managed to reduce the presence of fissures by plastic shrinkage, while the dosage of 0.5%, reduced the propagation of cracks, unlike concrete without addition of fibers, which had the presence of cracks.